Thismia mucronata (Thismiaceae), a new species from Southern Vietnam - Nuraliev, Maxim S.; Beer, Anton S.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P. (Phytotaxa, 2014)
Thismia mucronata, a new species of Thismiaceae, is described and illustrated. The species was discovered in 2013 during a botanical survey of a forest in the vicinity of Bao Loc town (Lam Dong province, Southern Vietnam). Thismia mucronata is characterised by vermiform roots and mitriform inner tepals. It differs from related species mainly by the short and appressed to each other appendages of inner tepals, which together resemble a short mucro, the narrow mitre without foveae, the almost horizontal annulus and the absence of interstaminal glands. A key to Vietnamese species of Thismia is provided.